Empowering Rural Development in Urbanizing China: A Government Intervention Perspective - Chen Chen; Shuang Liu (The Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Through a literature review and a case study, this research reviewed the rural development accompanying the urbanization process in China to summarize the evolution of country-level rural policies at different stages of the urbanization process. The authors state that the evolution of China’s urban-rural relationship has gone through five stages (i.e. the initial stage, the take-off stage, the accumulation stage, the urban-rural coordination stage, and the urban-rural integration stage) and has currently entered a period of slowing urbanization growth. However, there are still large differences in the level of urbanization development in various regions. Taking Shanghai, Suzhou, Chengdu, Chongqing, Zhejiang and several regions in central and western China as examples, the different responses of these cities and regions to the central government’s policies at different stages of urbanization were compared, as well as the rationality of policy intervention in rural areas. Finally, this paper re-conceptualizes the practice of rural development in the context of China’s rapid urbanization and proposes a government intervention development model adapted to the stages of urbanization. Abstrak. Melalui tinjauan literatur dan studi kasus, artikel ini mengulas pembangunan perdesaan dalam proses urbanisasi di Cina, dan merangkum evolusi kebijakan pedesaan tingkat negara pada berbagai tahap urbanisasi. Artikel ini percaya bahwa evolusi hubungan perkotaan-perdesaan China telah melalui lima tahap ‘awal, lepas landas, akumulasi, koordinasi perkotaan-perdesaan, integrasi perkotaan-perdesaan’ dan secara umum telah memasuki periode pertumbuhan urbanisasi yang melambat. Namun, tingkat perkembangan urbanisasi di berbagai daerah masih relatif besar. Selanjutnya, dengan mengambil contoh Shanghai, Suzhou, Chengdu, Chongqing, Zhejiang dan beberapa wilayah di Cina tengah dan barat, kami membandingkan respons yang berbeda dari daerah pada tahap pembangunan yang berbeda terhadap kebijakan pemerintah pusat serta rasionalitas intervensi kebijakan di daerah perdesaan. Terakhir, penelitian ini mengkonsep ulang praktik pembangunan perdesaan dalam konteks urbanisasi China yang pesat, dan mengusulkan model pembangunan intervensi pemerintah yang menyesuaikan dengan tahapan urbanisasi. Kata kunci. urbanisasi, pembangunan perdesaan, intervensi pemerintah, praktik lokal, China.